Effect of Dietary Supplementation of Crushed Flaxseed and Soybean Oil on Ovarian Functions in Postpartum Jersey Crossbred Cows - Deshmukh, S.G.; Ingawale, M.V.; Birade, H.S.; Thorat, M.G.; Kuralkar, S.V.; Rekhate, D.H.; Mode, S.G.; Chepte , S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The effect of dietary supplementation of crushed flaxseed and soybean oil on ovarian function in postpartum Jersey crossbred cows was studied. Total 30 postpartum normally calved cows from 2nd to 4th lactation were randomly divided into three equal groups. Cows from group T1 and T2 were fed with dietary supplementation of crushed flaxseed @ 15% of DM requirement from day 25 to day 70 postpartum and with soybean oil @ 3% of DM requirement of animal from day 50 to day 70 postpartum in addition to routine feed respectively, whereas cows from Group T3 was considered as control, supplemented with routine feed. Follicular dynamic study with the help of USG was carried out at 24 hrs interval before the first injection of GnRH of Ovsynch protocol and during Ovsynch protocol (Day 0 to Day 9) of synchronization, which was implemented from day 60 postpartum in all the groups. It was observed that mean number of class I follicles was significantly increased in T2 group, whereas the mean number of class II and total number of follicles were significantly increased in T1 and T2 groups on day 0. During the synchronization period the mean number of class I, class II, total numbers of follicles and preovulatory follicles size were significantly larger in T1 and T2 groups. It was concluded that dietary supplementation of crushed flaxseed and soybean oil helps in increasing class I, class II, total number of follicles and size of preovulatory follicle in crossbred cows.
Keywords: Follicular Dynamics; Flaxseed; Soybean oil; Postpartum cows; Ovsynch protocol